2016
DOI: 10.2337/db15-0629
|View full text |Cite
|
Sign up to set email alerts
|

The Brain–to–Pancreatic Islet Neuronal Map Reveals Differential Glucose Regulation From Distinct Hypothalamic Regions

Abstract: The brain influences glucose homeostasis, partly by supplemental control over insulin and glucagon secretion. Without this central regulation, diabetes and its complications can ensue. Yet, the neuronal network linking to pancreatic islets has never been fully mapped. Here, we refine this map using pseudorabies virus (PRV) retrograde tracing, indicating that the pancreatic islets are innervated by efferent circuits that emanate from the hypothalamus. We found that the hypothalamic arcuate nucleus (ARC), ventro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
76
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 51 publications
1
76
2
Order By: Relevance
“…65 Decreased neuronal glucosesensing in specific subregions of the hypothalamus induces glucose intolerance and deficient insulin secretion. 118 Thus, it is possible that defects in the neural mechanisms governing endocrine pancreatic function and glucose regulation contribute to CFRD.…”
mentioning
confidence: 99%
“…65 Decreased neuronal glucosesensing in specific subregions of the hypothalamus induces glucose intolerance and deficient insulin secretion. 118 Thus, it is possible that defects in the neural mechanisms governing endocrine pancreatic function and glucose regulation contribute to CFRD.…”
mentioning
confidence: 99%
“…Nevertheless, the mechanisms by which brain glucosesensing neurons regulate glucose homeostasis have remained unclear. This question is robustly addressed by the study by Rosario et al (13) in this issue of Diabetes. Using elegant improved retrograde pseudorabies viral (PRV) techniques, these investigators traced the connectivity from the brain to the pancreas to b-cells, using an inducible mouse insulin promoter Cre-recombinase construct.…”
mentioning
confidence: 57%
“…As with all good studies, the study by Rosario et al (13) should stimulate many further studies. For example, it will be of great interest to assess which subset of hypothalamic neurons mediates the effects of HK1 on insulin secretion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the classical study by Claude Bernard, which showed that an injury to the floor of the fourth cerebral ventricle caused hyperglycemia, the involvement of the nervous system in the regulation of pancreatic endocrine function and metabolic control has been shown in many studies [17][18][19]. At the same time, the precise innervation patterns of islets were unknown, particularly in humans [9].…”
Section: Introductionmentioning
confidence: 99%